PEMBERDAYAAN ALIANSI PETANI PADI ORGANIK BOYOLALI (APPOLI) DALAM PENGOLAHAN PASCA PANEN DAN PEMASARAN BERAS ORGANIK - Widiyanti, Emi; Santoso, Arief Iman (Universitas Negeri Yogyakarta, 2016)
Koperasi Sahabat Sejahtera as the division of post-harvest processing and marketing Appoli face some productions problems namely unavailability ofproduction equipment ranging from the drying process up to packaging. Postharvest equipment owned is the result of the hire from Tani Makmurusing system-processing services. This condition affected the efficiency of the business, the quantity of cooperative's income and the quantity of cooperative members. In order to overcome these problems some community services conducted as follows: (1) The introduction of post harvest handling technologies include: grading tool and blower mounted on a grading tool, table sorting, pallet, digital scales, water tested MD 7822; (2) increasing marketing quality through producing of a media campaign and improving the quality of the packages. The findings are Appoli able to increase production capacity and enhance its role in the development of organic rice and highly motivated to promote organic agriculture and increase farmers' income